1989
DOI: 10.1002/dev.420220608
|View full text |Cite
|
Sign up to set email alerts
|

Pubertal‐related changes influence the development of environment‐related social interaction in the male rat

Abstract: The influence of pubertal age on the differential effect of a familiar versus an unfamiliar environment on social interaction (SI) in pairs of male rats was evaluated. The decrease in SI induced by the unfamiliar environment in adult rats is considered an anxiety-related response. Intact male rats and male rats castrated at 19 days were tested for SI at 28, 35, and 60 days of age. The results revealed that in the intact rats, decreased SI in an unfamiliar environment was evident at 35 and 60 days but not at 28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
82
3
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(92 citation statements)
references
References 12 publications
5
82
3
2
Order By: Relevance
“…Exploration of the aversive, open arms of the elevated plus-maze was similar in adolescents and adults; while exploration of the aversive center of the novel open field was lower in peri-but not early adolescents than adults. These data concur with the finding that 4-week old Swiss Webster mice were no different from 8-week olds on the elevated plus-maze at baseline [48] (see also [21]), but not with another report that 7-week, but not 5-week old CD-1 mice showed lesser anxiety-like behavior in this test than adults [34], or with data variously reporting either relatively increased or decreased anxiety-like behavior in adolescents rats in both the elevated plus-maze, light/dark exploration test and the social interaction test [9,13,15,18,25,41,43,51]. Such differences may be due to methodological differences between studies.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Exploration of the aversive, open arms of the elevated plus-maze was similar in adolescents and adults; while exploration of the aversive center of the novel open field was lower in peri-but not early adolescents than adults. These data concur with the finding that 4-week old Swiss Webster mice were no different from 8-week olds on the elevated plus-maze at baseline [48] (see also [21]), but not with another report that 7-week, but not 5-week old CD-1 mice showed lesser anxiety-like behavior in this test than adults [34], or with data variously reporting either relatively increased or decreased anxiety-like behavior in adolescents rats in both the elevated plus-maze, light/dark exploration test and the social interaction test [9,13,15,18,25,41,43,51]. Such differences may be due to methodological differences between studies.…”
Section: Discussionmentioning
confidence: 87%
“…For example, adolescent rats have been found to exhibit either lesser, greater or normal levels of anxiety-like behavior in various behavioral assays as compared to adults [9,13,15,18,25,41,43,51]. In addition, a number of studies have shown that conditioned fear responses to footshock in rats emerges in the early adolescent period (reviewed in [6,23,24,47]).…”
Section: Introductionmentioning
confidence: 99%
“…Social behavior of adolescent and adult rats is sensitive to environmental factors, with, for example, social interactions being notably lower when animals are placed together in an unfamiliar relative to a familiar testing chamber [7,27,37]. An unfamiliar testing situation is traditionally viewed as an anxiogenic condition, and the decrease of social interactions under this condition has been used as an animal model of anxiety [5,6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Such environmentinduced social inhibition has been reported to differ as a function of age and sex, with young adolescent animals and adult females less affected by an unfamiliar test situation than older adolescents and adult males. For instance, male rats tested at postnatal day (P) 35 and P60 have been reported to demonstrate a reliable decrease in time spent in social interactions under unfamiliar test circumstances, whereas P28 males showed no suppression of social interactions under these test conditions [27]. In contrast, other researchers observed environment-dependent changes in social behavior as early as P21 when play fighting was assessed separately from other types of social behavior [36].…”
Section: Introductionmentioning
confidence: 99%
“…This can have resounding influences on adolescent behavior when maturation of the PFC and other frontal regions responsible for cognitive control, attention regulation, response inhibition, and other relatively advanced cognitive functions are relatively immature (Casey, Jones, & Hare, 2008) and emotional reactivity is high (Spear, 2013). As mentioned, this can result in behavior challenges for adolescents (increased risk-taking, reward-seeking, and novelty-seeking) and it can also become evident in increased negative peer-directed social interactions and increases in fighting with parents/guardians (Csikszentmihaly, 1977;Primus & Kellogg, 1989;Steinberg, 1989). This begins to assert that equipping adolescents with ways to manage not only their attention but also their emotional reactivity may be useful.…”
Section: Development Of Brain Matter In Adolescentsmentioning
confidence: 99%